2017
DOI: 10.1073/pnas.1711673114
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional visualization and a deep-learning model reveal complex fungal parasite networks in behaviorally manipulated ants

Abstract: SignificanceMicrobial parasites may behave collectively to manipulate their host’s behavior. We examine adaptations of a microbial parasite in its natural environment: the body of its coevolved and manipulated host. Electron microscopy and 3D reconstructions of host and parasite tissues reveal that this fungus invades muscle fibers throughout the ant’s body but leaves the brain intact, and that the fungal cells connect to form extensive networks. The connections are likened to structures that aid in transporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 37 publications
4
82
0
Order By: Relevance
“…The increased activation of the Ophiocordyceps secretome during manipulation by both species suggests a critical role for secreted compounds in modifying host behavior. This is in line with microscopy evidence demonstrating that fungal cells do not grow invasively into the ant's brain Fredericksen, 2017), but rather likely manipulate behavior peripherally by secreting neuroactive compounds. However, the specific functions of many putatively secreted proteins, upregulated during manipulation, have yet to be determined.…”
Section: Differentially Expressed Putative Fungal Effector Genessupporting
confidence: 87%
See 2 more Smart Citations
“…The increased activation of the Ophiocordyceps secretome during manipulation by both species suggests a critical role for secreted compounds in modifying host behavior. This is in line with microscopy evidence demonstrating that fungal cells do not grow invasively into the ant's brain Fredericksen, 2017), but rather likely manipulate behavior peripherally by secreting neuroactive compounds. However, the specific functions of many putatively secreted proteins, upregulated during manipulation, have yet to be determined.…”
Section: Differentially Expressed Putative Fungal Effector Genessupporting
confidence: 87%
“…A metabolomic study identified that the neuroprotectant ergothionine appears to be secreted by O. kimflemingiae during manipulation of C. castaneus . Indeed, neural tissues appear to be among the last tissues to be severely degraded , FREDERICKSEN & al. 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi form diverse relationships with viruses, algae, plants, animals, insects, and bacteria, and are critical to human health [15][16][17][18][19][20][21] . Filamentous fungi, in particular, are distinguished by their multinucleate such as Coprinopsis cinera for mushroom genetics, Agaricus bisporus for food, Schizophyllum commune for mushroom morphogenesis, and Phanerochaete chrysosporium for lignocellulosic biomass degradation, are different from the organisms that are used by industry, such as Ganoderma lucidum and Trametes versicolor 11,[58][59][60][61][62][63][64][65][66] .…”
Section: Introductionmentioning
confidence: 99%
“…These ants are prone to move to locations favourable to the development of the fungi, and move like robots: the 'zombie ants' (Hughes et al, 2011). The scariest and probably most interesting fact to be investigated is that it was shown that the brain of the ant is unaltered, so as the ant is able to move properly to the location chosen by the fungi (Fredericksen et al, 2017). Other examples have been also described.…”
mentioning
confidence: 99%